Pengaruh Profitabilitas, Kebijakan Utang dan Solvabilitas terhadap Nilai Perusahaan : Corporate Governance sebagai Variabel Pemoderasi - Siska Febriyanti; Akhmad Riduwan; Nur Handayani (Politeknik Ganesha Medan, 2025)
This research aims to examine and gain empirical evidence of the effect of profitability, debt policy, and solvability on firm value, with corporate governance as a moderating variable. Moreover, the population was Property companies listed on the Indonesia Stock Exchange with financial statement reports during 2014-2023. The data collection technique used purposive sampling with 325 data samples. Furthermore, the data analysis technique used moderated regression analysis with a hypothesis test using the t-test. The result concludes as follow: (1) profitability which is referred to as Return On Equity has a positive effect on firm value, (2)debt policy which is referred to as Debt to Assets Ratio has a negative effect on firm value, (3) solvability which is referred to as Debt to Equity Ratio does not effect firm value, (4) corporare governance moderates positively the effect of profitability on firm value, (5) corporare governance moderates positively the effect of debt policy on firm value, (6) corporare governance moderates negatively the effect of solvability on firm value.